Pemikiran Moral dan Faktor-Faktor Pribadi Mahasiwa terhadap Perilaku Moral - Tri Widyastuti; Meiliyah Ariani (Jurnal Bisnis Manajemen, 2015)
This study is aimed to examine the effect of moral reasoning and the student’s personal factors towards moral behaviour of accounting students in the four basic components to behave underlying of any moral actions or moral behaviour of an individual. In addition to that, it is also to examine the effect of accounting student demographic variables such as sex, Grade Point Average (GPA), and age towards their moral behaviour. The sample selected is done by using a purposive sampling method. Research data was collected from Accounting students of Pancasila University, Jakarta within academic enrollment year 2011/2012. The number of samples used are Accounting students of the 5th to 8th semester totaling 150 students. The analysis technique used is a multiple regression in SPPS ver.19. The results of the study shows moral reasoning and student’s personal factors influence positively and significantly towards the moral behaviour of accounting students simultaneously. Meanwhile, student’s personal factors which measured in the level of idealism, level of relativism in partial has positive and significant impact on student’s moral behaviour. And, others student’s personal factors are measured with locus of control, sex, GPA, and age has no significant influence towards moral behaviour partially.